2008
DOI: 10.1097/qad.0b013e3283136d68
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Toxoplasma gondii-specific immune responses in patients with AIDS starting HAART

Abstract: Among patients with low CD4 cell counts, high anti-Toxoplasma IgG titers were associated with LPR to Toxoplasma antigen. After starting antiretroviral therapy, the number of effector memory CD4 T cells and terminally differentiated CD8 T cells were associated with the restoration of Toxoplasma LPR and gamma-IFN production, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It is possible that they may have rapidly restored their cellular immunity, and subsequently mounted a strong immune response to Toxoplasma gondii [48]. The higher antibody titre in this case might reflect a more robust response to Toxoplasma gondii as reported previously [49], or a seroconversion closer to the time of NC testing [50] as opposed to a subclinical reactivation of Toxoplasma infection in the brain [51]. …”
Section: Discussionmentioning
confidence: 85%
“…It is possible that they may have rapidly restored their cellular immunity, and subsequently mounted a strong immune response to Toxoplasma gondii [48]. The higher antibody titre in this case might reflect a more robust response to Toxoplasma gondii as reported previously [49], or a seroconversion closer to the time of NC testing [50] as opposed to a subclinical reactivation of Toxoplasma infection in the brain [51]. …”
Section: Discussionmentioning
confidence: 85%
“…A low CD4 cell count has been identified as a significant risk factor in AIDS patients with CT (Tsambiras et al, 2001;de Boer et al, 2003;Sendi et al, 2006;Chen et al, 2009;Caby et al, 2010;Kung et al, 2011) due to impaired proliferative response to Toxoplasma antigen (Belanger et al, 1999), a decreased production of interferon  (Ullum et al, 1997), and it is found to be more common that IRIS develops in HIV-infected patients (Jevtović et al, 2005). Therefore, monitoring of CD4/CD8 T cells in patients on HAART might serve as a better marker for the restoration of T. gondii-specific immune responses than the total number of CD4 cells count (Furco et al, 2008). Immune reconstitution under HAART has been associated with a restoration of immune responses against T. gondii (Fournier et al, 2001).…”
Section: Immune Reconstitution Inflammatory Syndrome (Iris) -From Pasmentioning
confidence: 99%
“…A low CD4 + cell count has been identified as a significant risk factor in AIDS patients with CT93130–134 due to impaired proliferative response to Toxoplasma antigen135, a decreased production of interferon γ136, and IRIS develops more commonly in HIV-infected patients137. Therefore, monitoring of CD4 + /CD8 + T cells in patients on HAART might serve as a better marker for the restoration of T. gondii -specific immune responses than the total number of CD4 + cells count138. Immune reconstitution under HAART has been associated with a restoration of immune responses against T. gondii 139.…”
Section: Immune Reconstitution Inflammatory Syndrome (Iris) Associatementioning
confidence: 99%